Yorùbá Coastal Christian Communities: From the Evangelist Band Mission to the Zion and Holy Apostles Communities - Adégbọlá Tolú Adéfì (Yoruba Studies Review, 2021)
This article highlights the diversity of African Christianity in the Ìlàjẹ and Ìkále areas of present-day Ondo State, as well as in neighboring communities. It compares the successive religious movements led by E. M. Líjàdú and his Evangelist Band Mission, which represents an African missionary effort of the first generation in the Ikale and Ìlàjẹ areas, and the more recent Zion and Holy Apostles communities that have been established along the coast as independent Christian settlements under local spiritual leaders and kings. The article shows that there are certain similarities and differences between the successive movements. While the different conditions of the periods in which these movements operated, and the different conditions in which these religious activities were organized, matter, both movements offered their converts a new understanding of the world in which existing practices, were re-examined through an engagement with education and ‘modernity’ in a more general sense, and through existing forms of spiritual expression such as music, dance, and dress.